Curcuma yingdeensis (Zingiberaceae), a new species from China - Chen, Juan; Tong, Yi-Hua; Xia, Nian-He (Phytotaxa, 2019)
A new species of Curcuma L. subg. Curcuma (Zingiberaceae), C. yingdeensis N. H. Xia & Juan Chen, is described and illustrated. The new species is similar to C. phaeocaulis Valeton, but distinguished by creamy to pale yellow-colored rhizomes, narrower leaf blades, laxer inflorescences, smaller flowers, pink coma bracts with purple tips, pale green fertile bracts with brown tips and purple dots at the adnate portion, and sub-orbicular labellum with rounded lobes and two pale purple lines at the base.